The complete mitochondrial genome sequence from the longicorn beetle Obrium sp. (Coleoptera: Cerambycidae). (4th May 2017) - Song, Nan; Zhang, Hao; Yin, Xinming; Lin, Aili; Zhai, Qing
Abstract: The complete mitochondrial genome (mitogenome) of Obrium sp. was sequenced, which was the first representation from the longicorn beetle genus Obrium . The whole mitogenome is a typical circular DNA molecule of 15 680 bp, and has similar gene content and gene order to previously reported beetle species. In the sampled subfamilies of Cerambycidae, both Lamiinae and Cerambycinae were recovered with high supports in phylogenetic analysis. And the newly sequenced Obrium sp. was the sister group to Massicus raddei in Lamiinae.